Design for Sustainable Aging: Improving Design Communication Through Building Information Modeling and Game Engine Integration. (2015) - Wu, Wei; Kaushik, Ishan
Abstract: Accommodating the rapidly increasing senior population in the U.S. is a grand effort that necessitates sustainable solutions to address its social, economic and environmental impacts. From the building industry's standpoint, design for sustainable aging implies creating the physical and service environment that is resilient and adaptable to the needs associated with the aging process. The professional community has responded with well-conceived strategies such as universal and sustainable aging design. In practice, there is an inherent challenge in traditional paper-based design communication when professionals and clients have a hard time to understand each other at the desired level. Recent technological advancement in 3D modeling applications, exemplified by the prevalence of building information modelling (BIM), has reinvigorated sustainable aging design practices. Meanwhile, serious gaming has been gaining recognition as valuable enhancement to academic learning and professional training by effectively engaging participants with meaningful and programmable visualization and interaction. This study proposed to create a unique framework that leverages the integration of BIM and game engine to streamline and contextualize design communication in sustainable aging projects. A prototype framework, Design for Sustainable Aging (DfSA), was developed and discussed in this paper. Essentially, DfSA transforms a static design model into a robust 3D gaming environment wherein design information is preserved while user-centered and experience-based interactions with model components are achieved. DfSA holds the promise to improve design communication by establishing a brand new platform for design presentation meanwhile providing an experiential instrument to elucidate the design intention.